First record of Mayetiini (Coleoptera: Staphylinidae: Pselaphinae) from Brazil, with the description of a new macropterous and macrophthalmic species of Mayetia Mulsant & Rey, 1875 - Chaul, Júlio Cezar Mário; Lopes-Andrade, Cristiano (Zootaxa, 2022)
Mayetia atlantica sp. nov., the third Neotropical and first Brazilian species of Mayetiini Scheerpeltz, 1925, is described. It is the third macropterous and macrophthalmic species of the genus, alongside M. peruana Orousset, 1995 (Neotropical) and M. nepalensis Orousset, 1995 (Oriental). The new species is known from three forest remnants of the Brazilian Atlantic Forest, in the states of Espírito Santo, Minas Gerais (both in Southeast Brazil) and Bahia (Northeast Brazil), being the southernmost record of Mayetia in the New World. The description of M. atlantica is based mostly on females, but includes the first known male macropterous and macrophthalmic Mayetia. In this work, the tropical diversity of the genus is increased and its Neotropical distribution is greatly enlarged.